MiR-124-3p Combined with ANGPTL2 Has High Diagnostic Values for Obese and Nonobese Polycystic Ovary Syndrome. (14th June 2022) - Dai, Hongmei; Liu, Fangting; Lu, Jianshu; Yang, Yan; Liu, Pingping
Abstract : Polycystic ovary syndrome (PCOS) is a hormonal disorder that affects 5–20% of women of reproductive age. Interestingly, serum miR-124-3p and ANGPTL2 are differentially expressed in PCOS patients. Accordingly, this study set out to explore the clinical roles of serum miR-124-3p/ANGPTL2 in PCOS. Firstly, miR-124-3p/ANGPTL2 expression patterns were detected in the serum of 102 PCOS patients and 100 healthy subjects. miR-124-3p or/and ANGPTL2 diagnostic efficacy on PCOS was further analyzed, in addition to the measurement of lipid metabolism, glucose metabolism, sex hormone indexes, and inflammation levels. Correlations between serum miR-124-3p/ANGPTL2 expressions and age, BMI, Ferriman–Gallwey score, lipid metabolism, glucose metabolism, sex hormone indexes, TNF- α, and IL-6 in PCOS patients were determined. The expression correlation and binding relationship of ANGPTL2 and miR-124-3p were identified. In addition, miR-124-3p was downregulated and ANGPTL2 was upregulated in the serum of obese and nonobese PCOS patients. miR-124-3p expression was found to be negatively correlated with Ferriman–Gallwey score and serum total testosterone (T), and negatively related to prolactin (PRL). ANGPTL2 expression was positively correlated with FNS and inversely linked with PRL. TNF- α and IL-6 were negatively correlated with miR-124-3p, but positively correlated with ANGPTL2. Furthermore, there was a negative correlation and a targeting relationship between ANGPTL2 and miR-124-3p expression in the serum of obese and nonobese PCOS patients. Collectively, our findings indicated that miR-124-3p might target ANGPTL2 expression in obese and nonobese PCOS patients, and further underscored the diagnostic value of their combination.